2015
DOI: 10.1039/c4cc08527b
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol induces the formation of water-permeable defects in model bilayers of skin lipids

Abstract: We observe that ethanol can induce the formation of water-permeable defects in model bilayers of skin lipids and propose this as a new mechanism of action of ethanol as a membrane modulator.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 42 publications
3
30
0
Order By: Relevance
“…The maintenance of skin hydration depends on both the intercellular lipids which regulate the transport of water across the stratum corneum and a mixture of low‐molecular weight, water‐soluble compounds, such as amino acids, organic acids, urea, and inorganic ions, collectively known as NMFs. Short‐chain alcohols are penetration enhancers and known to exert pronounced effects on the intercellular lipids, including disruption of the lipid lamellae, lipid phase transition, and alterations in the lipid organization . Apart from these effects, short‐chain alcohols, and in particular, n ‐propanol, were recently shown to reduce the activity of phospholipase A2 (PLA 2 ), one of the key enzymes involved in the maintenance of barrier homeostasis and lipid processing in the skin .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maintenance of skin hydration depends on both the intercellular lipids which regulate the transport of water across the stratum corneum and a mixture of low‐molecular weight, water‐soluble compounds, such as amino acids, organic acids, urea, and inorganic ions, collectively known as NMFs. Short‐chain alcohols are penetration enhancers and known to exert pronounced effects on the intercellular lipids, including disruption of the lipid lamellae, lipid phase transition, and alterations in the lipid organization . Apart from these effects, short‐chain alcohols, and in particular, n ‐propanol, were recently shown to reduce the activity of phospholipase A2 (PLA 2 ), one of the key enzymes involved in the maintenance of barrier homeostasis and lipid processing in the skin .…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study following the om-TRIT protocol was to investi- The changes in the barrier function parameters after cumulative exposure to 60% n-propanol in a TRIT in healthy volunteers were initially studied by Kappes et al 18 Using the same exposure model, we recently showed significant impairment of the permeability barrier and alterations in the lipid organization. [22][23][24][25][26][27][28] Apart from these effects, short-chain alcohols, and in particular, n-propanol, were recently shown to reduce the activity of phospholipase A2 (PLA 2 ), one of the key enzymes involved in the maintenance of barrier homeostasis and lipid processing in the skin. 19 In an earlier publication, we provided first evidence for significant reduction in the stratum corneum NMF levels after om-TRIT with n-propanol and/or SLS and demonstrated that short-chain alcohols may cause skin dryness through interaction with both the skin lipids and reduction of NMF.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned earlier, researchers have used either CHARMM or GROMOS force eld to simulate the skin lipids. 25,31,32,43 Here, we have used GROMOS based force eld to capture the effect of ethanol concentration on skin lipid layer. The number of water and ethanol molecules for a particular ethanol mole fraction is given in Table 1.…”
Section: Unrestrained Simulationmentioning
confidence: 99%
“…The above observations of taking water molecules inside the bilayer interior could explain these experimental results. Thind et al 43 performed MD simulation of CER bilayer in presence of ethanol at various concentration and reported that water permeable defects were generated at higher ethanol concentration. Same researchers also reported the extraction of lipids from the CER lipid bilayer at very high concentration of ethanol.…”
Section: Unrestrained Simulationmentioning
confidence: 99%
“…More recently, it has been demonstrated that ethanol disrupted SC intercellular lipid structure, formed pores and promoted orthorhombic-(the most tightly packed lipid organization)to-hexagonal (a less tightly packed lipid organization) lipid phase transitions [18,19]. Also Thind et al [20] confirmed that ethanol induces water-permeable defects in models of SC lipids in vitro. However, the effects of ethanol on SC lipids in situ have not been investigated in depth.…”
Section: Introductionmentioning
confidence: 95%